CARDIAC REMODELING IN EXPERIMENTAL METABOLIC OBESITY: HISTOLOGICAL AND MORPHOMETRIC EVIDENCE OF EARLY MYOCARDIAL ALTERATIONS (International journal of artificial intelligence, 2025)
Metabolic obesity is a complex systemic condition leading to structural and functional alterations of the heart known as metabolic cardiomyopathy. Despite extensive studies on metabolic disorders, the morphological mechanisms of myocardial remodeling under chronic metabolic overload remain insufficiently characterized. Objective: This study aimed to evaluate the morphological and morphometric features of myocardial remodeling in a rat model of diet-induced metabolic obesity and to determine correlations between metabolic and structural parameters of the heart. Methods: an experimental model of metabolic obesity was reproduced in 20 male Wistar rats fed a high-fat and high-carbohydrate diet (HFD) for 12 weeks. Myocardial tissue was examined histologically using hematoxylin and eosin (H&E) staining, followed by morphometric assessment of cardiomyocyte cross-sectional area, left ventricular wall thickness, and the extent of interstitial fibrosis. Body weight, heart mass index, and serum lipid profile were measured. Statistical analysis included Student’s t-test and Pearson correlation. Results: chronic exposure to HFD caused significant increases in body weight (+38.6%), heart mass index (+18.4%), left ventricular wall thickness (+19.8%), and cardiomyocyte cross-sectional area (+33.4%) compared with controls (p < 0.01). The relative area of interstitial fibrosis increased 2.6-fold (p < 0.001). Strong positive correlations were found between body weight and cardiomyocyte size (r = 0.78; p < 0.001) and between total cholesterol and fibrosis area (r = 0.65; p < 0.01). Histologically, the myocardium showed hypertrophy, cytoplasmic vacuolization, nuclear hyperchromasia, and focal interstitial edema, indicating early structural disorganization and fibrosis. Conclusion: prolonged consumption of a high-fat, high-carbohydrate diet induces adaptive–pathological myocardial remodeling manifested by cardiomyocyte hypertrophy, interstitial fibrosis, and vascular wall thickening. These morphological changes correlate closely with body mass and lipid metabolism disorders, reflecting the early stages of metabolic cardiomyopathy.